A photo-crosslinked proteinogenic hydrogel enabling self-recruitment of endogenous TGF-β1 for cartilage regeneration - Xiaojing Ju; Xingzhi Liu; Yu Zhang; Xu Chen; Mimi Chen; Huaishuang Shen; Yonghai Feng; Jisheng Liu; Miao Wang; Qin Shi (Smart Materials in Medicine, 2022)
Cartilage regeneration is crucial to the functional reconstruction of damaged or degenerated joints, involving a variety of biological factors. Transforming growth factor-beta 1 (TGF-β1) play an important role in chondrogenesis and cartilage regeneration. In this study, we developed a novel photo-crosslinked Gelatin methacryloyl (GelMA) hydrogel modified with TGF-β1-affinity peptide (HSNGLPL), which can self-absorb with TGF-β1, and investigated the effect of GelMA/HSNGLPL (Pep-HGelMA) hydrogels on chondrogenesis and cartilage regeneration. In vitro, Pep-HGelMA hydrogel scaffolds were confirmed to recruit endogenous TGF-β1, and induced mesenchymal stem cells into chondrocytes. In vivo, more cambium and smooth surface was grossly observed at the injured sites of knee joint implanted with Pep-HGelMA hydrogels than those of other groups four and eight weeks post-operation. Micro-CT and histological evaluation further demonstrated more cartilage tissue and higher scores in Pep-HGelMA-implanted knees. In addition, more cartilage-like tissue indicators including collagen II and less matrix metalloproteinase 13 were also observed. All the data suggests that the photo-crosslinked hydrogel scaffold characterized by excellent mechanical properties and biocompatibility, can accelerate cartilage tissue repair by recruiting TGF-β1 automatically, which provides a promising system for cartilage repair in clinical application.